2016
DOI: 10.7600/jpfsm.5.81
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and oxidative stress in osteoarthritis

Abstract: Osteoarthritis (OA) is one of the most common age-related degenerative joint disorders. In addition to aging, various lifestyle related factors, such as obesity and overuse of joints, have been recognized as major risk factors for OA. It has been revealed that mechanical force acting on articular cartilage induces chondrocytes to produce excess amounts of reactive oxygen species (ROS), which are known to be an OA-related catabolic factor. In addition, it has been reported that mechanical stress-induced ROS dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The MDA level was used as an indicator of the lipid peroxidation level and was also associated with an increase in free radical production ( Mas-Bargues et al, 2021 ). In the case of surgically induced knee OA, oxidative stress also increased due to mechanical force ( Yui et al, 2016 ). Also, oxidative stress was associated with an elevated level of obesity due to the presence of immoderate adipose tissue ( Pottie et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MDA level was used as an indicator of the lipid peroxidation level and was also associated with an increase in free radical production ( Mas-Bargues et al, 2021 ). In the case of surgically induced knee OA, oxidative stress also increased due to mechanical force ( Yui et al, 2016 ). Also, oxidative stress was associated with an elevated level of obesity due to the presence of immoderate adipose tissue ( Pottie et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that NO synthesis was actively progressed in OA chondrocytes [25]. In other words, OA chondrocytes might undergo some cellular events like inflammatory response, apoptosis or oxidative stress [26]. Moreover, increased expression of iNOS and NO have been found in vivo in inflammatory, septic arthritis and in patients with rheumatoid arthritis [27].…”
Section: Discussionmentioning
confidence: 99%